The Effect of Tax Avoidance on Firm Value in Non-Cyclical Consumer Sector Companies Listed on the Indonesia Stock Exchange 2018-2022 - Darmawan, Davi Judha; Raainaa, Nural Achmad; Sofianti, Evin (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study intends to examine the impact of tax evasion on the value of firms in the Non-Cyclical Consumer sector listed on the Indonesia Stock Exchange from 2018 to 2022. The study includes a population of 125 companies and a sample of 22 companies. The findings indicated that the tax evasion variable had a non-significant negative impact on business value, however the state ownership and foreign ownership variables had a substantial negative impact on firm value. This study's addition to the literature is based on empirical research carried out in the Non-Cyclical Consumer sector in Indonesia. It focuses on examining the impact of tax evasion, local ownership, and foreign ownership on business value. This study addresses a research vacuum by emphasizing the significance of examining the impact of tax evasion, local ownership, and foreign ownership on business value, a topic that has not received extensive attention in existing literature.